2016
DOI: 10.1177/1474704916659483
|View full text |Cite
|
Sign up to set email alerts
|

Life History Theory and Exploitative Strategies

Abstract: Exploitative strategies involve depriving others of resources while enhancing one's own. Life history theory suggests that there are individual differences (life history strategy) and environmental characteristics (life history contingencies [LHCs]) that influence the use of exploitative strategies. However, past work manipulating LHCs has found mixed evidence for the influence of this information on exploitative behavior. We present three studies that help clarify the effects of this type of information. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The item "For me, the environment we live in is unpredictable" developed by Reynolds and McCrea [44], was used to measure how participants perceived the general unpredictability of their environment. Participants rated this item on a 7-point Likert scale, ranging from 1 (strongly disagree) to 7 (strongly agree).…”
Section: Perceived General Environmental Unpredictabilitymentioning
confidence: 99%
“…The item "For me, the environment we live in is unpredictable" developed by Reynolds and McCrea [44], was used to measure how participants perceived the general unpredictability of their environment. Participants rated this item on a 7-point Likert scale, ranging from 1 (strongly disagree) to 7 (strongly agree).…”
Section: Perceived General Environmental Unpredictabilitymentioning
confidence: 99%
“…Maslow considered that sense of security was the feeling of individual happiness, trust, and love and being loved (Maslow et al, 1945). To provide just one theoretical angle, there is a growing literature on the relationship among negative life events and social relationship from the life history theory perspective (Reynolds and McCrea, 2016). Research of this tradition has found links between negative life events and social connections with family and friends (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%